Análisis del costo de producción a partir del costeo absorbente y directo de la línea legys de ropa deportiva en la microempresa Etnia Sport de la ciudad de Palmira- Valle del Cauca (2022)
The present work had as objective, the analysis of the production costing from the absorbent and direct costing of the Legys line of sportswear of the company Etina Sport of the city of Palmira Valle, dedicated to the manufacture and commercialization of sportswear.